Bank Deposits and Their Impact on Supporting the Financial Stability of Banks - Al-Shimmery, Arshed Abdul Ameer Jasem (Opción, 2019)
The study aims to address the problem of the decrease in the volume of deposits in the Iraqi banking sector and its impact on the financial stability of commercial banks via a set of statistical methods. As a result, there is a positive relationship between bank deposits and financial stability, as is the case of a positive relationship between financial stability and other economic components. In conclusion, there are two main factors that lead to financial instability: excessive investments, large speculation and thus their effects on other economic variables